Performance of Hevea brasiliensis on Haplic Acrisol soil as affected by different source of fertilizer. - Mokhatar, Shafar Jefri; Wan Daud, Wan Mohamed Noordin (Center of Promoting Ideas, 2011)
Rubber has been planted widely in South East Asia since more than a century ago. Rubber usage has been discovered and developed for various usages. This situation induces demand for natural rubber to increase steadily . Nitrogenous fertilizer is very important in growing stage. This study will provide details about effect of fertilizer, nitrogenous on Haplic Acrisol soil which has been classified as first class in soil suitability for rubber tree. Through this study, it was found that urea performs equally as well when compared to ammonium sulphate at the equivalent of 10% N. However, in terms of cost per unit nitrogen, urea is very much cheaper; the cost of urea is around USD350-500 per ton, compared to the cost of ammonium sulphate which is USD 5670-6190 per ton. The dosage of urea used should be controlled because it can cause adverse effects on the plant if over applied. The leaves of plant will scorch, the soil will crust, and the plants will be vulnerable to infection. The study provides information for further improvement in rubber nursery management.